Research on the Mural Flora of Sidhi City in Madhya Pradesh, India - Singh , Vivek Kumar; Salim , Mohammad (Recent Trends in the Study of Botanical Research Volume - 1, 2023)
The current chapter discusses the mural floristic composition of Sidhi city, Madhya Pradesh. A total of 60 mural plants were documented, including bryophytes and pteridophytes. The angiospermic mural flora comprised 51 genera from 29 distinct families. Additionally, two bryophyte species and two pteridophyte species were also observed in the study.